2014
DOI: 10.1136/bmjopen-2013-004619
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of dapagliflozin combined with hypoglycaemic drugs in treating type 2 diabetes mellitus: meta-analysis of randomised controlled trials

Abstract: ObjectivesThis meta-analysis aimed to evaluate whether dapagliflozin is synergistic with other antidiabetic drugs without body weight gain.SettingRandomised controlled trial (RCT) reports were retrieved from PubMed, Cochrane Library, EMBASE, ClinicalTrials.gov, Google Scholar and Google. Eligible RCTs were selected according to the criteria (including types of participants, intervention, outcomes) and assessed by the Cochrane risk of bias tool and GRADEpro software for evidential quality. Meta-analysis on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 30 publications
9
50
2
4
Order By: Relevance
“…In addition, HbA1c reductions were greater in patients with poor glycemic control. These real-world treatment effects are comparable to results of dapagliflozin randomized clinical trials 715,1821,26…”
Section: Discussionsupporting
confidence: 70%
“…In addition, HbA1c reductions were greater in patients with poor glycemic control. These real-world treatment effects are comparable to results of dapagliflozin randomized clinical trials 715,1821,26…”
Section: Discussionsupporting
confidence: 70%
“…A meta-analysis 308 of RCTs of 12-104 weeks duration showed that dapagliflozin (2.5-10.0 mg per day) improved HbA 1c , FPG and weight compared with placebo when used as an add-on therapy to metformin, insulin, thiazolidinediones, sulfonylureas or metformin ± sitagliptin (mean difference between groups −0.52%, 95% CI −0.60% to −0.45%, −1.52 mmol/l, 95% CI −1.75 mmol/l to −1.29 mmol/l and −1.61 kg, 95% CI −1.97 kg to −1.26 kg, respectively). The reductions in HbA 1c and FPG compared with placebo were generally similar with different background treatments, but were greatest when dapagliflozin was added to a sulfonylurea (−0.96%, 95% CI −0.86% to −0.52% and −1.47 mmol/l, 95% CI −1.86 mmol/l to −1.08 mmol/l) 308 . The largest between-group difference in weight change was seen when dapagliflozin was added to insulin (−2.45 kg, 95% CI −2.99 kg to −1.92 kg) 308 .…”
Section: Pharmacodynamicsmentioning
confidence: 92%
“…The reductions in HbA 1c and FPG compared with placebo were generally similar with different background treatments, but were greatest when dapagliflozin was added to a sulfonylurea (−0.96%, 95% CI −0.86% to −0.52% and −1.47 mmol/l, 95% CI −1.86 mmol/l to −1.08 mmol/l) 308 . The largest between-group difference in weight change was seen when dapagliflozin was added to insulin (−2.45 kg, 95% CI −2.99 kg to −1.92 kg) 308 .…”
Section: Pharmacodynamicsmentioning
confidence: 92%
“…The observed effects of a 0.6% change in HbA 1c were comparable with those reported in meta-analyses and systematic reviews of pharmaceutical agents for treating diabetes and is considered to be clinically significant. 29,30 Self-efficacy has been strongly associated with better adherence to diabetes treatment recommendations and improved patient outcomes. 31 Current evidence suggests that incorporating self-efficacy in health assessment and interventions to increase a person's perceived ability to self-manage is beneficial for improved diabetes care.…”
Section: Discussionmentioning
confidence: 99%